Troponin T elevation in acute aortic syndromes: Frequency and impact on diagnostic delay and misdiagnosis. Issue 7 (November 2016) - Vagnarelli, Fabio; Corsini, Anna; Bugani, Giulia; Lorenzini, Massimiliano; Longhi, Simone; Bacchi Reggiani, Maria Letizia; Biagini, Elena; Graziosi, Maddalena; Cinti, Laura; Norscini, Giulia; Taglieri, Nevio; Semprini, Franco; et al.
Aims: Despite troponin assay being a part of the diagnostic work up in many conditions with acute chest pain, little is known about its frequency and clinical implications in acute aortic syndromes (AASs). In our study we assessed frequency, impact on diagnostic delay, inappropriate treatments, and prognosis of troponin elevation in AAS. Methods and results: Data were collected from a prospective metropolitan AAS registry (398 patients diagnosed between 2000 and 2013). Cardiac troponin test, using either standard or high sensitivity assay, was performed according to standard protocol used in chest pain units. Troponin T values were available in 248 patients (60%) of the registry population; the overall frequency of troponin positivity was 28% (ranging from 16% to 54%, using standard or high sensitivity assay respectively, p = 0.001). Troponin positivity was frequently associated with acute coronary syndromes (ACS)-like electrocardiogram findings, and with a twofold increased risk of long in-hospital diagnostic time (odds ratio (OR) 1.92, 95% confidence interval (CI) 1.05–3.52, p = 0.03). The combination of positive troponin and ACS-like electrocardiogram abnormalities resulted in a significantly increased risk of in-hospital delay/coronary angiography/antithrombotic therapy due to a misdiagnosis of ACS (OR 2.48, 95% CI 1.12–5.54, p = 0.02). However, troponin positivity was not associated with in-hospital mortality (OR 1.63, 95% CI 0.86–3.10, p = 0.131). Conclusions: Troponin positivity was a frequent finding in AAS patients, particularly when a high sensitivity assay was employed. Abnormal troponin values were strongly associated with ACS-like electrocardiogram findings and with in-hospital diagnostic delay but apparently they did not influence in-hospital mortality.